Viability study of ethylene (C2H4) as an alternative fuel for gasoline engine - Abdul Latiff, Zulkarnain; Abdul Aziz, Azhar; Supriyo, Bambang; Said, Mazlan (Faculty of Mechanical Engineering, 2008)
Ethylene (C2H4) a very important gaseous hormone commonly used in agriculture to enhance the ripening of fruits and to stimulate rubber tree to yield more latex. In industry, polymerized ethylene, which produced polyethylene, also called polythene; the world’s most widely used plastic. As a source of hydrocarbons, the physical properties such as high in energy content compared to gasoline and highly flammable (classified by EU) are strong indications that the gas can be easily combusted. This paper is intended to publish the possibility of using the mentioned gas as a fuel in for gasoline-powered vehicle. The methodology used to evaluate the viability of the gas is by experimental approach. The test done on the engine as a unit by itself (using engine test bed) and engine fitted to a vehicle where a chassis dynamometer is engaged. As for on the road test, a gas kit was developed, complete with electronic control unit (ECU) to ensure proper controlled amount of ethylene being induced to the engine. The data mapping in the ECU is obtained from the performance test done on the engine test bed. Gas kit develop is being customized and fine-tuned to suit with the properties of ethylene and gasoline engine design. This is vital in order to come up with an optimized fuel-handling system to ensure maximum performance attained. All the work undertaken and performance data obtained were compared to gasolinefuelled engine. In other words, the presentation of experimental results for ethylene is always compared to gasoline.